An Evolutionary Game-Based Trust Cooperative Stimulation Model for Large Scale MANETs - Xiao Wang; Yinfeng Wu; Yongji Ren; Renjian Feng; Ning Yu; Jiangwen Wan (International Journal of Distributed Sensor Networks)
In order to realize a methodical, effective cooperative stimulation for MANETs and search dynamic trust cooperative stimulation scheme in environment under a high malicious ratio, we have proposed an evolutionary game-based trust cooperative stimulation model for large scale MANETs in this paper. First, the system members' pluralistic behavior for MANETs has been covered by means of constructing the complete multirisk level strategy space. Then a trust-preferential strategy has been built through trust numerical value mapping technology, which achieves the aim that the malicious action is effectively constrained to avoid a low trust level. Furthermore, the mobility probable parameters and information propagation error matrix are introduced into game model, and the convergence condition between optimum strategy which represents payoff maximization principle and trust-preferential strategy is deduced through evolutionary analyzing finally. Both theoretical analysis and simulation experiments have demonstrated that our model can effectively stimulate cooperation among members and meanwhile be robust under the condition where the environment is harsh under a high original malicious ratio in large scale MANETs.